REM SLEEP DEPRIVATION-INDUCED OXIDATIVE STRESS AND ITS ATTENUATION BY TEPHROSIA PURPUREA (L.,) IN DISCRETE REGIONS OF RAT BRAIN - Selvaraj, Prakash; Shanmuganathan, Annadurai; Selvaraj, Saravanan; Mani, Babukumar; Govindaraj, Sakthivel; Rajan, Dr. Ravindran (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study is to assess the antioxidant activity of Tephrosia purpurea (TP) in 72 h REM sleep deprivation (RSD). Nowadays, plants are used as therapeutic agents in the wide range of clinical applications. The present investigation is focused on the antioxidant activity of the ethanolic extract of TP on 72 h RSD induced changes in discrete regions of rat brain. Methods: In this study, the plant (leaf) sample collected and ethanolic extraction were done using Soxhlet apparatus. Five groups of Wistar strain male albino rats were used in this study. Each group comprises 6 rats and multiple platform models used for RSD. The values were statistically analyzed using one-way analysis of variance followed by Tukey's post hoc test for multiple comparison methods. The significance level was kept at p<0.05. The 72 h RSD-induced changes in discrete regions were investigated and verified by measuring the activity of superoxide dismutase (SOD), lipid peroxidation (LPO), catalase (CAT), glutathione peroxidase (GPx), levels of reduced glutathione (GSH), Vitamin C, and Vitamin E in different regions of the rat brain, and plasma corticosterone level. Results: This study confirmed that the leaf extract of TP effectively normalized the increased corticosterone, LPO, SOD, CAT, GPx, and decreased GSH, Vitamin C, and Vitamin E levels as a result of 72 h RSD exposure. Conclusion: The plant examined and possessed remarkable antioxidant activity; hence, the isolation of compounds from this plant leaves may develop a novel and natural phytomedicine for stress-induced diseases.